Article 14 of WHO FCTC: gaps in implementation & recommendations - Suzanne Nethan; Dhirendra Sinha; Kumar Chandan; Ravi Mehrotra (Tobacco Induced Diseases, 2018)
Background Article 14 of the WHO Framework Convention on Tobacco Control (FCTC) deals with demand reduction measures concerning tobacco dependence and cessation. This paper identifies the gaps in its implementation globally, with appropriate recommendations to fulfill the same.